STUDI TENTANG TANGGAP BOCAH (TABO) DALAM PENANGGULANGAN DEMAM BERDARAH DENGUE MELALUI PEMBERANTASAN SARANG NYAMUK DI PUSKESMAS SLEMAN TAHUN 2013 - , ROLAND ARUNG PIRADE, Dr. Wahyudi Istiono, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Some villages in sub-district of Sleman, such as Caturharjo Village had high amount of morbidity of dengue Hemorrhagic Fever (DHF) and ABJ (result of larva free rate) was lower than 85%, whereas the PSN (elimination of mosquito breeding places) had been organized. Therefore innovation were made by the officer of Puskesmas (Primary Health Center) of Sleman and the society by implemented TABO (Children Action) which the cadres are the Children Cadre. TABO was expected to decrease the morbidity of DHF and increase the ABJ in Caturharjo Village. Objective: To understand the implementation of TABO in preventing DHF in Caturharjo Village. Particular objective were to understand: 1) input of TABO, 2)process of TABO, 3) output of TABO Method: The study was qualitative with case study design. Primary data were obtained by doing in-depth interview with 16 respondents and also by doing observation. Secondary data obtained from Department of Health of Sleman District. Result: After implementing TABO morbidity has decreased by a half & ABJ has increased than previous years. Conclusion: Implementation of TABO in preventing DHF in Caturharjo Village ran effectively, seen from the decreasing of morbidity and the increasing of the result of larva free rate significantly in Caturharjo Vilage. Keywords: ABJ, Morbidity, DHF, Department of Health, Larvae Monitoring Team, Puskesmas, TABO